EFFECTIVE POLITICAL REFORMS AS A FACTOR IN ENHANCING THE STATE IMAGE: THE EXPERIENCE OF THE REPUBLIC OF KOREA AND UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the relationship between effective politicalreforms and the enhancement of a state’s image, using the cases of the Republic ofKorea and the Republic of Uzbekistan. It argues that in contemporary internationalrelations, the image of a state is shaped not only by economic growth, military power,or cultural attractiveness, but also by the quality of political institutions, the degree oftransparency in public administration, the effectiveness of anti-corruption policy, thedigitalization of public services, the protection of human rights, and the government’scapacity to respond to public demands. The Republic of Korea demonstrates theexperience of transition from an authoritarian model to a democratic, technologicallyadvanced, and internationally recognized state. Uzbekistan, in turn, has beenimplementing a large-scale program of political, legal, and administrative reformssince 2016, aimed at forming the image of an open, modernizing, and responsible state.The article provides a comparative analysis of the two cases, identifies commonpatterns and distinctive features, and formulates conclusions regarding the significanceof consistency, institutional sustainability, and public legitimacy of reforms forstrengthening the international image of the state.
Keywords: political reforms, state image, Republic of Korea, Uzbekistan, modernization, digital government, anti-corruption policy, public administration, international reputation..